Analisis Disparitas Putusan Hakim Dalam Penjatuhan Pidana Terhadap Tindak Pidana Perjudian - HM. Siregar (PRANATA HUKUM, 2014)
According to the Kartini Kartono at her book âSocial Patologyâ (2005), Criminal Law used to solve social problems, expecially to crime prevention, as one of the society desease and social patology form like gambling case. Gambling at the history process from generation to generation, it is not easy to be prevented, although the reality showed that result from gambling by goverment can be used for development activities. Article 1 Undang- undang No 7 Tahun 1974 about Penertiban Perjudian, regarded as reasonable and legitimate, but very threaten the social society. Legal doctrine ruled that âRes Judicate Pro Veritate Hebeturâ it means that everything is decided by the judge was correct, although at the reality it is not true until it binding and cannot be cancelled by other court. As court function, behavior of law enforcement, expecially Integrated Justice System and more expecially is judge behavior, became one of the main barometer for a state law to know how affectuation law and legislation.Reality, at the court, judge can be decided criminal offense according to the gambling actionÂ but different (disparitas) although at the same case.